The Calibration of the Second Primary International Reference Preparation for Thromboplastin (Thromboplastin, Human, Plain, Coded BCT/253) - Thomson, Jean M; Tomenson, J A; Poller, L (Thrombosis and Haemostasis, 1984)
An international collaborative exercise has been undertaken to calibrate a replacement for the first WHO primary international reference preparation (IRP) for thromboplastin. The replacement preparation is a lyophilised batch of British Comparative Thromboplastin (BCT/253, human plain) for use in the Quick prothrombin time test. Seventeen centres participated. The experimental design, calibration model and statistical analysis were based on the recommended WHO procedure. As a result of this calibration exercise an International Sensitivity Index (ISI) of 1.1 has been assigned to the preparation by WHO and it has been officially recognised as the second primary IRP for thromboplastin.The calibration of BCT/253 is an essential link in a new hierarchical structure for the standardisation of the prothrombin time. The aim is to provide a uniform international system of reporting prothrombin time results using International Normalised Ratios (INR) derived from the ISI of individual thromboplastins.
Keywords: International reference thromboplastin; Thromboplastin calibration; Prothrombin time standardisation